Empowering Primary School Teachers Through Mobile Learning to Break Educational Stereotypes - Adesina, Abiodun Ezekiel; Putri, Husmayani Muny; Syarif, Eka Aghnia (LPPM Universitas Jambi, 2025)
This community engagement study aimed to empower primary school teachers in Oyo Town to integrate mobile learning as a tool for breaking educational stereotypes and enhancing inclusive pedagogy. The initiative responded to persistent structural and attitudinal barriers in Nigerian primary education by offering stereotype-reduction training through mobile technology. Employing a sequential exploratory mixed-methods approach, the program involved 250 teachers from public and private schools across four local government areas. Qualitative data were gathered via semi-structured interviews, followed by quantitative validation through structured questionnaires. The findings revealed that teachers—particularly younger and less experienced ones—held strong positive perceptions of mobile learning's potential to challenge stereotypes, with no significant differences by gender, qualification, or school type. However, implementation was hindered by policy ambiguity, infrastructural deficits, and limited technological readiness. The study underscores the value of localized, community-responsive interventions in promoting digital inclusion and educational equity. Future research should investigate the long-term impact of mobile learning on classroom practice and explore peer-mentoring strategies to bridge generational gaps among teachers. The study recommends targeted investments in digital infrastructure, supportive policies, and differentiated capacity-building to ensure scalable integration of mobile learning in diverse primary school contexts.